Surge in solar powered homes : experience in off-grid rural Bangladesh - Khandker, Shahidur R.; Samad, Hussain A., 1963- (Directions in development (Washington, D.C.). Energy and mining., 2014)
Bangladesh has the world's fastest growing, off-grid solar home system (SHS) coverage. In the past decade, the number of SHS installations has risen phenomenally--from a five-year target of 50,000 in 2003 to 50,000 a month in 2013, with support from the World Bank and other development partners. Even so, only 10 percent of off-grid households have been reached, suggesting ample room for continued expansion. Given the recent surge in SHS adoption, a key policy issue is whether the partial subsidy provided under the current program, implemented by the Infrastructure Development Company Limited)